PENGARUH FAKTOR PENGISTIRAHATAN TERNAK SEBELUM PEMOTONGAN TERHADAP KUALITAS DAGING SAPI DI RUMAH POTONG HEWAN OEBA BERDASARKAN NILAI PH DAN DAYA IKAT AIR - Ety Rambu B. Anamuli; Annytha I.R. Detha; Diana A. Wuri (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2016)
Meat is one of food that has balanced nutritional composition and is in great demand by the public. Therefore, quality is should be noticed. One of the physical traits that affect the quality of meat is the pH value and water holding capacity (WHC). The purpose of this study was to determine the quality of meat from rested cattle and not rested cattle by measuring the pH value of the meat after 1 hour, 6 hours and 24 hours postmortem and WHC measurements after 12hours postmortem. The number of samples tested consisted of 40 samples of meat from cattle rested and 40 samples of meat from the not rested cattle. The results showed that 40 samples of meat from cattle rested produce 75% a good quality meat, 7,5% pale, soft, exudative (PSE) quality meat, and 17,5% dark, firm, dry (DFD) quality meat based on the pH value and has an average value 36.36% of cooking loss so that it has a lower WHC value. While 40 samples of meat from not rested cattle produce 82.5% DFD quality meat, and produce 17.5% of good quality meat based on the pH value and has an average value 30.85% of cooking loss so that it has a higher WHC value. Therefore, it can be concluced that the rested cattle are most likely to produce a good quality meat than the not rested cattle.